Log horizon : the West Wind Brigade. 1 - Touno, Mamare (Yen Press, 2016)
A disastrous expansion of the online RPG Elder Tales has trapped thousands of players inside the game world--among them, the members of a guild known as the West Wind Brigade. Amid the chaos and confusion, danger stalks the guild's girls! Will Soujirou, the guild master, be able to the protect them? The West Wind Brigade's struggles are just beginning!